2016
DOI: 10.2215/cjn.12731215
|View full text |Cite
|
Sign up to set email alerts
|

Association of mGFR of the Remaining Kidney Divided by Its Volume before Donation with Functional Gain in mGFR among Living Kidney Donors

Abstract: Background and objectives The predictors of long-term renal function in living kidney donors are currently discussed. Our objectives were to describe the predictors of functional gain of the remaining kidney after kidney donation. We hypothesized that GFR of the remaining kidney divided by volume of this kidney (rk-GFR/vol) would reflect the density of functional nephrons and be inversely associated with functional gain of the remaining kidney.Design, setting, participants, & measurements We conducted a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…This observation is in accordance with what was reported regarding the relationship between eGFR and mGFR among potential donors [19]. Moreover, we recently published two studies showing that mGFR (and not eGFR) divided by the volume of the remaining kidney could be used to predict functional gain of the remaining kidney following donation [20] and that measured GFR could not be predicted precisely by calculators or equations for nearly 60% of donors [19]. For these reasons, we think that eGFR cannot replace mGFR in living donor screening.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in accordance with what was reported regarding the relationship between eGFR and mGFR among potential donors [19]. Moreover, we recently published two studies showing that mGFR (and not eGFR) divided by the volume of the remaining kidney could be used to predict functional gain of the remaining kidney following donation [20] and that measured GFR could not be predicted precisely by calculators or equations for nearly 60% of donors [19]. For these reasons, we think that eGFR cannot replace mGFR in living donor screening.…”
Section: Discussionsupporting
confidence: 92%
“…First, irrespective of age at donation, eGFR on average steadily increased for the subsequent few years (Figures 1 and 2 age and BMI at donation were inversely correlated with the change in GFR. 28 Similarly, we found that both age and BMI at donation, were inversely correlated with postdonation eGFR (Figure 2A). with our data, this information suggests that GFR increases for many years postdonation, and that once the age-related fall in GFR begins, donors have more reserve than population data might suggest.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, Lenihan et al, studying postdonation glomerular dynamics, reported increased plasma flow and GFR over 6 years (27). Although also finding an increase in measured GFR for the first 5 years after donation, Courbebaisse et al found that age and body mass index at donation were inversely correlated with the change in GFR (28). We found a similar association between both age at donation and BMI at donation, with postdonation eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-eight articles received full-article screening. Of these, we excluded the following: 22 studies were not relevant; 10 studies only included patients with kidney disease (and not kidney donors); 24-33 4 studies did not report Pearson’s r and data could not be extracted; 34-37 and 1 study compared SRF with SRV in mL/min rather than as a percent and was inappropriate for pooling. 38 The 21 eligible studies are described in Table 1 and were mathematically combined in meta-analysis along with the results from the London, Ontario chart review.…”
Section: Resultsmentioning
confidence: 99%